The effect of carbon nanofibers on transverse cracking in carbon fiber reinforced polymer: A 3D finite element modeling and simulation. Issue 26 (26th October 2022) - Bian, Pei-Liang; Qing, Hai
Abstract: The influence of carbon nanofibers (CNFs) on carbon fiber (CF) reinforced polymer (CFRP) is investigated in this study. A program is developed to generate the finite element model (FEM) for the nanocomposites. The randomness of both CNFs and CF in CFRP is considered. The effects of volume fraction of CNFs and CFs, as well as interfacial strength are analyzed numerically. The improvement in strength and toughness of composites under different loading conditions is investigated. It shows that CNFs lead the redistribution of stress in the matrix, which releases stress concentration between CFs and polymer and increases the initial damage threshold.